Exposure to lemongrass essential oil and its components causes behavior and respiratory disturbs in Anticarsia gemmatalis - Brügger, Bruno Pandelo; Plata-Rueda, Angelica; Wilcken, Carlos Frederico [UNESP]; Souza, Laila Salomé Araújo de; Serrão, José Eduardo; Carvalho, Amélia Guimarães; Zanuncio, José Cola; Martínez, Luis Carlos (Taylor & Francis, 2021)
Anticarsia gemmatalis is the most important soybean pest in various countries of America controlled mainly with synthetic insecticides. Effective management alternatives to control and avoid of insecticide resistance are needed against this pest. The toxicity, behavioral response, and respiration of A. gemmatalis larvae exposed to lemongrass essential oil (LEO) and its components were investigated. The principal components of LEO were neral, citral, and geranyl acetate with 31.5%, 26.1%, and 2.27% abundance, respectively. Larvae contact toxicity was found 36 h after exposure with LEO (LD50= 14.7 µg insect−1), citral (LD50= 4.56 µg insect−1), and geranyl acetate (LD50= 15.9 µg insect−1). Insects exposed to LEO and its components reduced locomotion and orientation to treated surfaces. Also, A. gemmatalis larvae reduced their respiration after treatment with LEO and components. These results demonstrate that LEO, citral, and geranyl acetate cause toxic and repellent effects on A. gemmatalis, indicating their potential to control this soybean pest.
Keywords: Botanical insecticide; gas chromatography; repellency; respiration rate; terpenoids; toxicity